Archaeobotanical evidence for climate as a driver of ecological community change across the anthropocene boundary. (15th April 2014) - Ellis, Christopher J.; Yahr, Rebecca; Belinchón, Rocío; Coppins, Brian J.
Abstract The biodiversity response to climate change is a major focus in conservation research and policy. Predictive models that are used to project the impact of climate change scenarios – such as bioclimatic envelope models – are widely applied and have come under severe scrutiny. Criticisms of such models have focussed on at least two problems. First, there is an assumption that climate is the primary driver of observed species distributions ('climatic equilibrium'), when other biogeographical controls are often reliably established. Second, a species' sensitivity to macroclimate may become less relevant when impacts are down‐scaled to a local level, incorporating a modifying effect of species interactions structuring communities. This article examines the role of different drivers (climate, pollution and landscape habitat structure) in explaining spatial community variation for a widely applied bioindicator group: lichen epiphytes. To provide an analysis free of 'legacy effects' (e.g. formerly higher pollution loads), the study focused on hazel stems as a relatively short‐lived and recently colonized substratum. For communities during the present day, climate is shown to interact with stem size/age as the most likely explanation of community composition, thus coupling a macroclimatic and community‐scale effect. The position of present‐day communities was projected into ordination space for eight sites in England and compared to the position of historical epiphyte communities from the same sites, reconstructed using preserved hazel wattles dating mainly to the 16th Century. This comparison of community structure for the late‐ to post‐Mediaeval period, with the post‐Industrial period, demonstrated a consistent shift among independent sites towards warmer and drier conditions, concurrent with the end of the Little Ice Age. Long‐term temporal sensitivity of epiphyte communities to climate variation thus complements spatial community patterns. If more widely applied, preserved lichen epiphytes have potential to generate new baseline conditions of environment and biodiversity for preindustrial lowland Europe.